2001
DOI: 10.1108/00400910110399247
|View full text |Cite
|
Sign up to set email alerts
|

E‐learning developments and experiences

Abstract: Over the past five years, institutions of higher education in Australia and overseas have been investing increasingly larger sums of money in a range of e-learning initiatives. RMIT University, for example, has allocated AUS$50 million over the period 1999-2001 for aligning information technology to the needs of the core business of the university[1] and The University of Melbourne has allocated $12 million since 1997 for multimedia enhanced teaching and learning development[2]. This increased investment in e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(158 citation statements)
references
References 7 publications
5
145
0
8
Order By: Relevance
“…However, lack of interpersonal contact with other users and lack of communication, support and feedback from module co-ordinators which lead to low motivational levels was one of the major disadvantages perceived by SMTEs from online learning. It is also interesting to note that a study by Alexander (2001) reported that adequate access to technical support is essential for learners in achieving successful learning outcomes. The survey results gave no indication that information on technological skill (i.e.…”
Section: Figure 4 Preferred Online Learning Contentmentioning
confidence: 99%
“…However, lack of interpersonal contact with other users and lack of communication, support and feedback from module co-ordinators which lead to low motivational levels was one of the major disadvantages perceived by SMTEs from online learning. It is also interesting to note that a study by Alexander (2001) reported that adequate access to technical support is essential for learners in achieving successful learning outcomes. The survey results gave no indication that information on technological skill (i.e.…”
Section: Figure 4 Preferred Online Learning Contentmentioning
confidence: 99%
“…Alexander [12] proposes a more comprehensive framework for the design, development and implementation of e-learning systems in higher education. Bolliger [1] investigates key factors influencing student satisfaction with online courses.…”
Section: Factors Affecting the E-learningmentioning
confidence: 99%
“…E-learning is a general term that is used to describe the learning process in which information and communication technology could be utilized [1,2]. Recently, most of the elearning interfaces are largely dependent on text and graphics as a mean of information delivery means.…”
Section: Introductionmentioning
confidence: 99%